ANALYSIS OF THE INFLUENCE OF MACROECONOMIC VARIABLES ON INFLATION: THE VECM APPROACH - Damayanti, Sekar Ayu; Jalunggono, Gentur (Transpublika Publisher, 2022)
Inflation is defined as a condition where prices increase. Inflation is a monetary phenomenon in a country where its fluctuations will cause economic turmoil. In the economy, inflation is a combination of aspects of the balance of the goods market, money market, and labor market. This study analyzes the relationship between macroeconomic variables, namely economic growth, interest rates, and the money supply which are expected to affect the movement of the inflation rate in Indonesia in 1989-2019. This study uses the Vector Error Correction Model (VECM) method after showing the existence of cointegration in testing with the VAR model. Forecasting results show that inflation responds positively to interest rates and the money supply and gives a negative response to economic growth. This means that inflation in Indonesia is sensitive to shocks in macroeconomic variables.